2012
DOI: 10.4081/mrm.2012.637
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns in severe hemoptysis requiring bronchial artery embolization

Abstract: Background: Although some authors have suggested that there is some seasonal periodicity in hemoptysis, temporal patterns of hemoptysis have been poorly investigated. The aim of this study is to describe the temporal pattern of severe hemoptysis which required bronchial artery embolization (BAE). Methods: All consecutive patients with at least one episode of hemoptysis which required BAE during a 13-year period were included. Recurring hemoptysis requiring BAE in a patient with previous embolization was includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several conditions such as tuberculosis, cancer, or bronchiectasis may lead to clinically significant hemoptysis. Some authors have suggested that there is some seasonal periodicity of hemoptysis [ 1 3 ] or have described its association with respiratory tract infections [ 4 7 ], or with climatic parameters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several conditions such as tuberculosis, cancer, or bronchiectasis may lead to clinically significant hemoptysis. Some authors have suggested that there is some seasonal periodicity of hemoptysis [ 1 3 ] or have described its association with respiratory tract infections [ 4 7 ], or with climatic parameters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%